Impact of Interleukin-18 Genetic Polymorphisms on the Susceptibility to Hashimoto’s Thyroiditis in Iraqi Patients. - Abdulfattah, Assia Khaldon; Allami, Risala H.; Shareef, Saja Ali (Journal of Advances in Medical & Biomedical Research)
Background & Objective: Hashimoto’s Thyroiditis (HT) is one of the prevalent autoimmune thyroid disorders. This disease is characterized by chronic lymphocytic infiltration and progressive thyroid tissue destruction. The development of HT is influenced by the complex interplay between immunological and genetic factors. This study aimed to investigate the association between gene polymorphisms of Interleukin-18 (IL-18), a pro-inflammatory cytokines, and susceptibility to HT in Iraqi population. In particular, three single nucleotide polymorphisms (SNPs): (rs1946518, rs187238, and rs1946519) were examined and analyzed to enhance the understanding of the genetic contribution of IL-18 polymorphisms to HT pathogenesis, thereby supporting the improvement of early diagnosis, treatment, and prevention strategies. Materials & Methods: The total number of participants included in this study was 100. The patients who were diagnosed with HT were 50 and the healthy were 50 representing the control group. The study was conducted using standard molecular biology methods including genotyping of the samples via sequencing techniques. Statistical methods were subsequently applied to analyze the results of the distribution of alleles and genotypes. Results: We observed no significant difference in the genotype or allele frequency of rs1946518 between HT patients and healthy controls. The results of rs187238 demonstrate no genetic variation in the study population: all samples exhibited the homozygous wild-type genotype, suggesting that this SNP may not be polymorphic in the Iraqi population. Similarly, rs1946519 displayed no significant differences among the patient and control groups. Conclusion: In conclusion, the examined IL-18 gene polymorphisms showed a non-significant correlation with HT in the observed Iraqi samples. It is recommended to continue the research on this topic with larger sample sizes and include more diverse groups.